Software Defect Prediction Analysis Using Machine Learning Techniques - Viranchee V Dave (International Journal of Computer Sciences and Engineering, 2025)
Software Quality is a critical aspect of any software. Software Defect Prediction directly impacts quality and has gained significant popularity in recent years. Defective software modules have a massive impact on software quality, leading to cost overruns, delayed timelines, and higher maintenance costs. This paper analyzes the most popular and widely used Machine Learning algorithms: ANN (Artificial Neural Network), PSO (Particle Swarm Optimization), DT (Decision Trees), NB (Naive Bayes), and LC (Linear Classifier). The five algorithms were analyzed using the KEEL tool and validated using k-fold cross-validation. Datasets were obtained from the open-source NASA Promise dataset repository. Seven datasets were selected for defect prediction analysis. Classification was performed on these datasets and validated using 10-fold cross-validation. The results demonstrated the Linear Classifier`s dominance over other algorithms in terms of defect prediction accuracy.